Karakteristik Kepemimpinan Kiai Berlandaskan Nilai-nilai Pancasila - Ria Fajriya; Machdum Bachtiar; Anis Fauzi; Iis Sholihat (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The current phenomenon of national leadership has resulted in a degradation of the quality and alignments of leaders. This can be seen from the rampant radical actions in society that are motivated by religion and culture, rampant corruption, violations of law and human rights, economic policies that do not side with the people, and various other problems that arise. Everything happened due to the leadership crisis and the absence of role models from leaders who live and are based on the values of Pancasila. Leadership must have honesty with oneself (integrity), sincere responsibility (compassion), knowledge (cognizance), courage to act by beliefs (commitment), trust in yourself and others (confidence), and the ability to convince others (communication) in building an organization. Leaders can use their influence because of their personal characteristics, reputation, or charisma to influence the behavior of subordinates in a variety of situations.Leadership based on pancasila values will not be separated from the conceptual building of the five precepts in it. How the first divine precepts are placed as the basis of morality. As a precept that is causa prima (the source of other precepts) then inevitably the leader referred to here is a leader who is Godly, moral and truly carries out his existence in the world to prosper nature and the diverse humans in it.Kyai is a central element in the life of pesantren, not only because Kyai is the main buffer for the continuity of the education system in pesantren, but also because the figure of Kyai is a reflection of the values that live in the student community.